2002
DOI: 10.4218/etrij.02.0102.0102
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Fault Tolerance Protocol with Backup Foreign Agents in a Hierarchical Local Registration Mobile IP

Abstract: A Mobile IP allows IP hosts to move between different networks without changing their IP addresses. Mobile IP systems supporting local registration were introduced to reduce the number of times a home registration with the remotely located home agent was needed. The local registration Mobile IP scheme enhanced performance by processing registration requests of mobile nodes at a local agent. The local registration approach may affect other aspects of the Mobile IP systems such as fault tolerance. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…The procedure of data transmission in conventional IP-based mobility management schemes, such as MIPv6, HMIPv6 and FMIPv6, is discussed in many publications such as [6][7][8][9][10][11][12][13]. When a CN sends packets with a MN's home-ofaddress (HoA), the home agent (HA) in the MN's home network intercepts and forwards them to the MN's CoA with IP-in-IP tunneling.…”
Section: Data Transmission Between Mn and Cnmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure of data transmission in conventional IP-based mobility management schemes, such as MIPv6, HMIPv6 and FMIPv6, is discussed in many publications such as [6][7][8][9][10][11][12][13]. When a CN sends packets with a MN's home-ofaddress (HoA), the home agent (HA) in the MN's home network intercepts and forwards them to the MN's CoA with IP-in-IP tunneling.…”
Section: Data Transmission Between Mn and Cnmentioning
confidence: 99%
“…After intensive and broad research efforts, some fast handoff protocols have been reported, such as the hierarchical mobile IPv6 (HMIPv6) [7] and the fast handover for mobile IPv6 (FMIPv6) [8]. The HMIPv6 protocol is designed to minimize handoff latency and the amount of signaling to the home agent (HA) and correspondent node (CN) by allowing the MN to locally register in a mobile anchor point (MAP) domain [7,[10][11][12][13]. Another fast handover scheme is the FMIPv6 which allows the use of layer 2 triggers, based on the handoff anticipation, to decrease the handoff latency and packet losses by introducing a tunnel between the previous care-of-address (PCoA) and the new care-of-address (NCoA) [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As propostas de tolerânciaà falha dos Agentes de Mobilidade que empregam redundância de hardware [3], [4] apresentam um desempenho melhor quando comparadas com aquelas em que membros de redundância são dinamicamente alocados no caso de falhas. Istoé verdadeiro quando a carga de tráfego gerenciada por esse hardware redundante não ultrapassa a sua capacidade.…”
Section: Trabalhos Relacionadosunclassified
“…In mobile communication systems, the exchange of information with mobile terminals should be facilitated regardless of their locations [1], [2]. To meet this requirement, the network should have well-defined functions to manage the location information and to page the target mobiles in an efficient way.…”
Section: Introductionmentioning
confidence: 99%